ANTROPONATIONCENTERIZM PHILOSOPHICAL WORLD VIEW OF I. FRANCO - Возняк, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the unity of a human being and a nation, universal and national entity in the worldview of Ivan Franko. The latter is defined by the author as anthroponationalcentrism. The paper highlights the evolution of social and philosophical views of the Ukrainian thinker from the admittance of social issue having priority significance over the national issue to the priority of national in the solving of everyday problems of people.